Pilkada Langsung Dan Pilkada Tidak Langsung Dalam Perspektif Fikih Siyasah (UINSI Samarinda, 2016)
Direct and Indirect Regional Head Election (Pilkada), has been a long debate in the life of a democratic society in Indonesia. With Islam as a religious social background of the majority of the people of Indonesia, this makes the debate cannot be separated from the Islamic jurisprudence (fiqh). This paper is to compare the two electoral systems in light of Islamic constitutionalism (fiqh syasah). This study uses the theory of maqasid sharia of the maslaha as a tool to analyze the comparison of the two electoral systems. The findings of this study suggest that there are some positive things on one side, and some negative things on the other side on each system of direct election and indirect election. Taking into account the benefit of both the local election systems, the study concluded that direct election has more benefits that outweigh the indirect election. Some of the public benefits include: the strengthening of the people's sovereignty and avoid injustice in society at large as part of the learning aspects of politics and government. Second, it will build a litigious society and law enforcement officers who act decisively and are nonpartisan, which in turn creates a reverent attitude of the people towards the leader. In the field of socio-economic, public and private investors’ confidence in the system and the results of the election will increase due to the political stability that is essential for the economy.Keywords: Regional head election in Indonesia, direct election, indirect election, fiqh siyasah in Islam